Financial transaction tax : the case of the European Union - Bis??ta, Anna (Routledge, 2026)
"The financial crisis of 2008 renewed interest in implementing a financial transaction tax on a global scale. As no consensus was reached, in 2011, the European Union suggested imposing a European Union financial transaction tax (EU FTT). - The publication discusses this original EU concept of taxing financial transactions and contains a detailed description of the efforts made by selected EU Member States within the framework of the mechanism of enhanced cooperation between 2013-mid 2024 in the field of financial transaction taxation. It also discusses the financial transaction taxes recently adopted at the national level in 3 EU countries that have taken part in the enhanced cooperation mechanism: France, Italy and Spain. Additionally, a review of global scientific research has been presented indicating the possible effects of the FTT. In the last chapter, the author presents the results of her own research on the impact of introducing the FTT on derivatives trading on financial market in Italy and her concept of taxing financial transactions. The book may become recommended reading for scholars and researchers of taxes and financial markets, the history of economic thought and the problems of the functioning of the EU, and will also find an audience among employees of financial and tax departments, tax administration staff, practitioners in the finance industry as well as politicians and governing authorities interested in implementing the FTT"-- Provided by publisher.
Keywords: Finance -- European Union countries.; Taxation -- European Union countries.; Investments -- Taxation -- European Union countries.; elektronické knihy; electronic books